(untitled) (Journal of Enam Medical College, 2016)
Pagets disease (PD) of the bone is a chronic metabolic disorder involving increased bone turnover with abnormal repair, leading to bony deformities and associated pain. It is characterised by a disturbance in bone modelling and remodelling because of increased osteoclastic activity followed by improper osteoblastic repair. Although PD of bone is an uncommon entity, axial skeleton involving pelvic bones, spine and skull are the commonest sites. Here we report a case of 65-yearold postmenopausal female who presented with generalised bone pain and subsequently was diagnosed as a case of Pagets disease and managed accordingly. J Enam Med Col 2016; 6(2): 106-109